Climate and Land Cover Change Transform Functional Identity and Reduce Functional Diversity in European Grasslands - Chang Liu; Stef Haesen; Jürgen Dengler; Denys Vynokurov; Idoia Biurrun; Łukasz Kozub; Iwona Dembicz; Alireza Naqinezhad; Béla Tóthmérész; Dariia Borovyk; Franz Essl; Juan Antonio Campos; et al. (Global Ecology and Biogeography, 2026)
Aim European grasslands rank among the most species‐rich ecosystems at small spatial scales, yet their biodiversity and functioning face significant threats from climate change and land‐use intensification. Functional traits more effectively explain ecosystem functions (EFs) than species identity or diversity. This study examines how future climate and land cover changes will shape grassland functional composition, addressing gaps in trait‐environment relationships and large‐scale functional predictions. Location Europe. Time Period 1971–2000 and 2081–2100. Major Taxa Studied 4406 distinct grassland plant species. Methods We used Boosted Regression Trees to model trait‐environment relationships based on vegetation plot data from sPlotOpen, GrassPlot, and the Nordic‐Baltic Grassland Vegetation Database (NBGVD). We mapped the 17 trait community‐weighted means (CWMs) and three functional richness (FRic) metrics under historical conditions and two future climate scenarios to assess temporal and spatial changes in grassland functional composition. Results The trait–environment relationships are highly trait‐dependent: structural and size‐related traits such as plant height, leaf area and seed number were consistently well‐predicted, whereas other traits were less well predicted. Mean annual temperature emerged as the strongest predictor of grassland functional composition. Climate and land cover change were predicted to drive significant spatial shifts in trait CWMs and FRic. Specifically, leaf area was predicted to decline in the Baltic Sea region and Pannonian Basin, while plant height was expected to increase across Europe. Seed number was predicted to rise at higher latitudes and in mountainous regions. Moreover, FRic was expected to decrease in temperate grasslands but increase at high latitudes and mountainous regions. Main Conclusions Our findings reveal distinct spatial patterns in functional shifts, reflecting plant adaptation to future environmental conditions. The increase in FRic at high latitudes and mountainous regions also signals ecosystem transitions that may pose additional threats to further complicate grassland conservation efforts.

Impacts of abundance and habitat area weighting in allocating species trends to habitats - Robin J. Pakeman (Environmental Monitoring and Assessment, 2025)
The dynamics of species depend on the management of their habitats. However, in the absence of good habitat monitoring data for many types of species, reliance has been placed on identifying habitats seeing marked changes in biodiversity through combining trends in their associated species into a habitat level metric. Several data sources on species occupancy, abundance within different habitats, and habitat area for two example taxa, bryophytes and lichens, were linked to assess how different methods of allocating existing species’ abundance trends to habitats influenced the habitat statistics. In general, trends through time were similar, but the method of allocation had an impact on the absolute values of the Distribution Index that summarises weighted occupancy. Allowing generalists to contribute equally to specialist species in a habitat gave higher values of habitat level Distribution Index than methods which weighted species according to abundance in that habitat and habitat area. There were also impacts on the analysis of long-term and short-term trend data, with the more complex methods, including abundance within habitats and extent of habitat, detecting more differences between habitats, and, for some habitats, changing positive trends for bryophytes to no significant trend or even negative for sparsely vegetated habitats. If species trend data is to be used for identifying habitats where biodiversity trends are marked, then it is clear that weighting species, such that their total weight across the analysis is the same, is necessary. Developing the precise means to achieve that needs careful thought and the creation of a robust method that works across different species groups, but using unweighted data could lead to erroneous conclusions as they are so dependent on the dynamics of widespread species.

Comparing stakeholder perspectives and biodiversity models in assessing scenarios of management change - Robin J. Pakeman; Alba Juárez-Bourke; Scott Herrett; Alice Hague; Anja Byg; Altea Lorenzo-Arribas; Anke Fischer; Laura MacLean; Keith Marshall; Gillian Donaldson-Selby; Alison J. Hester; Antonia Eastwood (Journal of Environmental Management, 2025)

Limited spatial co-occurrence of wildfire and prescribed burning on moorlands in Scotland - Debbie Fielding; Scott Newey; Robin J. Pakeman; Dave Miller; Zisis Gagkas; Keith Matthews; Stuart W. Smith (Biological Conservation, 2024)

Factors affecting severity of wildfires in Scottish heathlands and blanket bogs - Noemi A.L. Naszarkowski; Thomas Cornulier; Sarah J. Woodin; Louise C. Ross; Alison J. Hester; Robin J. Pakeman (Science of The Total Environment, 2024)

The contribution of geographically common and rare species to the spatial distribution of biodiversity - Hannah J. White; Caroline M. McKeon; Robin J. Pakeman; Yvonne M. Buckley (Global Ecology and Biogeography, 2023)
Motivation and aim Mapping the spatial distribution of biodiversity is critical for understanding its fundamental drivers (e.g. speciation, environmental filtering) as well as for conservation assessment. An important dimension of this topic is how the distributions of subsets of species contribute to the overall distribution of biodiversity. Although studies have previously investigated the role of geographically common and rare species in determining these patterns, their respective contributions appear to vary between studies. Knowing which species contribute disproportionately to the spatial distribution of biodiversity enables the identification of key indicator species for biodiversity assessments across large areas and is important for prioritising areas for conservation actions. An extensive review of the literature was carried out to synthesise research on how geographic rarity contributes to spatial patterns of biodiversity. We identify potential explanations for the discrepancies in findings between studies and identify opportunities for further research. Results Many studies on the contribution of geographic commonness and rarity to the spatial distribution of biodiversity focus on species richness. A prevalent view is that common (widespread) species contribute disproportionately, although this is not ubiquitous across studies due to factors such as the geographic extent from which relative rarity is quantified. We identify research pathways that will further improve our knowledge of how geographically common and rare species shape the spatial distribution of biodiversity including the impact of spatial scale on species contributions and the incorporation of biodiversity components beyond taxonomic alpha diversity, that is functional and phylogenetic diversity. Main conclusions Future research should incorporate multiple biodiversity components and model scale dependency. This will further our knowledge on the underlying processes that shape the spatial variation of biodiversity across the planet and help inform biological surveys and conservation activities.

Complementary effects of biodiversity and ecosystem services on spatial targeting for agri-environment payments - Alessandro Gimona; Margaret McKeen; Andrea Baggio; Enrico Simonetti; Laura Poggio; Robin J. Pakeman (Land Use Policy, 2023)

How long do bracken (Pteridium aquilinum (L.) Kuhn) control treatments maintain effectiveness? - Ilgın Akpınar; Josu G. Alday; Emma Cox; H.A. McAllister; Michael G. Le Duc; Robin J. Pakeman; Rob H. Marrs (Ecological Engineering, 2023)

Variability in mycorrhizal status of plant species is much larger within than between plots in grassland and coastal habitats - Martin Bitomský; Hanno Schaefer; Robin J. Pakeman; Jitka Klimešová; Lars Götzenberger; Martin Duchoslav (Oecologia, 2022)

Increased grazing drives homogenisation but reduced grazing increases turnover in upland habitat mosaics - Robin J. Pakeman; Debbie A. Fielding (Biodiversity and Conservation, 2021)
Many ecosystems are grazed by livestock or large, wild herbivores and exist as mosaics of different vegetation communities. Changing grazing could have an impact on heterogeneity as well as on composition. A long-term, large-scale grazing experiment that maintained existing low-intensity sheep grazing, tripled it, removed it and partially substituted sheep grazing by cattle grazing was set up on a mosaic of upland vegetation types. The impact of changing grazing regimes was assessed in terms of changes in temporal and spatial species and functional beta diversity. Removal of grazing had the highest impact on species replacement, whilst increased grazing was closest to maintaining the original species complement. Wet heath and Molina mire had the lowest turnover, but wet heath showed the highest changes in unidirectional abundance as it contained species capable of increasing in abundance in response to changing grazing intensity. Agrostis-Festuca and Nardus grasslands displayed the highest level of balanced species replacement reflecting their more dynamic vegetation. In functional terms, there was no clear separation of communities based on their grazing preference, all were relatively resistant to change but Nardus grassland was the most resistant to the removal of grazing. The increased offtake associated with increased grazing led to a degree of homogenisation as grazing tolerant species associated with preferred communities increased in the unpreferred ones. Decisions about grazing management of the uplands involve many trade-offs, and this study identified potential trade-offs between stability and homogenisation to add to existing ones on the biodiversity of different groups of species and on ecosystem services.

Mycorrhizal status is a poor predictor of the distribution of herbaceous species along the gradient of soil nutrient availability in coastal and grassland habitats - Martin Bitomský; Robin J. Pakeman; Hanno Schaefer; Jitka Klimešová; Solvita Rūsiņa; Zdeňka Lososová; Pavla Mládková; Martin Duchoslav (Mycorrhiza, 2021)

Buffering effects of soil seed banks on plant community composition in response to land use and climate - Jan Plue; Hans Van Calster; Inger Auestad; Sofía Basto; Renée M. Bekker; Hans Henrik Bruun; Richard Chevalier; Guillaume Decocq; Ulf Grandin; Martin Hermy; Hans Jacquemyn; Anna Jakobsson; et al. (Global Ecology and Biogeography, 2021)
Aim Climate and land use are key determinants of biodiversity, with past and ongoing changes posing serious threats to global ecosystems. Unlike most other organism groups, plant species can possess dormant life‐history stages such as soil seed banks, which may help plant communities to resist or at least postpone the detrimental impact of global changes. This study investigates the potential for soil seed banks to achieve this. Location Europe. Time period 1978–2014. Major taxa studied Flowering plants. Methods Using a space‐for‐time/warming approach, we study plant species richness and composition in the herb layer and the soil seed bank in 2,796 community plots from 54 datasets in managed grasslands, forests and intermediate, successional habitats across a climate gradient. Results Soil seed banks held more species than the herb layer, being compositionally similar across habitats. Species richness was lower in forests and successional habitats compared to grasslands, with annual temperature range more important than mean annual temperature for determining richness. Climate and land‐use effects were generally less pronounced when plant community richness included seed bank species richness, while there was no clear effect of land use and climate on compositional similarity between the seed bank and the herb layer. Main conclusions High seed bank diversity and compositional similarity between the herb layer and seed bank plant communities may provide a potentially important functional buffer against the impact of ongoing environmental changes on plant communities. This capacity could, however, be threatened by climate warming. Dormant life‐history stages can therefore be important sources of diversity in changing environments, potentially underpinning already observed time‐lags in plant community responses to global change. However, as soil seed banks themselves appear, albeit less, vulnerable to the same changes, their potential to buffer change can only be temporary, and major community shifts may still be expected.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Phenological changes of the most commonly sampled ground beetle (Coleoptera: Carabidae) species in the UK environmental change network - Gabor Pozsgai; John Baird; Nick A. Littlewood; Robin J. Pakeman; Mark R. Young (International Journal of Biometeorology, 2018)

Calcium plus magnesium indicates digestibility: the significance of the second major axis of plant chemical variation for ecological processes - Pavla Mládková; Jan Mládek; Stanislav Hejduk; Michal Hejcman; Robin J. Pakeman (Ecology Letters, 2018)
Plant variation in nutrient concentrations encompasses two major axes. The first is connected to nitrogen (N) and phosphorus (P), reflects growth rate and has been designated as the leaf economics spectrum ( LES ) while the second follows the gradient in calcium (Ca) and magnesium (Mg) and mirrors cell structural differences. Here, we tested in grasslands whether the sum Ca + Mg concentrations is a better indicator of digestibility than LES constituents. Structural equation modelling revealed that the total effect size of N (0.30) on digestibility was much lower than that of Ca + Mg (0.58). The N effect originated predominantly from sampling date (biomass ageing), while the Ca + Mg effect largely from phylogenetic composition (proportion of monocots). Thus, plant variation in partially substitutable divalent cations seems to play a significant role in biomass digestion by ruminants. This finding contests, together with litter decomposition studies, the prominent role of the LES for understanding both fundamental ecological processes.

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Continuing influences of introduced hedgehogs Erinaceus europaeus as a predator of wader (Charadrii) eggs four decades after their release on the Outer Hebrides, Scotland - John Calladine; Elizabeth M. Humphreys; Lucy Gilbert; Robert W. Furness; Robert A. Robinson; Robert J. Fuller; Nick A. Littlewood; Robin J. Pakeman; Johanne Ferguson; Charles Thompson (Biological Invasions, 2017)

How to Replicate the Functions and Biodiversity of a Threatened Tree Species? The Case of Fraxinus excelsior in Britain - Ruth J. Mitchell; Robin J. Pakeman; Alice Broome; Joan K. Beaton; Paul E. Bellamy; Rob W. Brooker; Chris J. Ellis; Alison J. Hester; Nick G. Hodgetts; Glenn R. Iason; Nick A. Littlewood; Gabor Pozsgai; et al. (Ecosystems, 2016)

Species composition of coastal dune vegetation in Scotland has proved resistant to climate change over a third of a century - Robin J. Pakeman; Jim Alexander; Joan Beaton; Rob Brooker; Roger Cummins; Antonia Eastwood; Debbie Fielding; Julia Fisher; Sarah Gore; Richard Hewison; Russell Hooper; Jack Lennon; et al. (Global Change Biology, 2015)
Climate change is expected to have an impact on plant communities as increased temperatures are expected to drive individual species' distributions polewards. The results of a revisitation study after c. 34 years of 89 coastal sites in Scotland, UK, were examined to assess the degree of shifts in species composition that could be accounted for by climate change. There was little evidence for either species retreat northwards or for plots to become more dominated by species with a more southern distribution. At a few sites where significant change occurred, the changes were accounted for by the invasion, or in one instance the removal, of woody species. Also, the vegetation types that showed the most sensitivity to change were all early successional types and changes were primarily the result of succession rather than climate‐driven changes. Dune vegetation appears resistant to climate change impacts on the vegetation, either as the vegetation is inherently resistant to change, management prevents increased dominance of more southerly species or because of dispersal limitation to geographically isolated sites.

Combination of herbivore removal and nitrogen deposition increases upland carbon storage - Stuart W. Smith; David Johnson; Samuel L. O. Quin; Kyle Munro; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Global Change Biology, 2015)
Ecosystem carbon (C) accrual and storage can be enhanced by removing large herbivores as well as by the fertilizing effect of atmospheric nitrogen (N) deposition. These drivers are unlikely to operate independently, yet their combined effect on aboveground and belowground C storage remains largely unexplored. We sampled inside and outside 19 upland grazing exclosures, established for up to 80 years, across an N deposition gradient (5–24 kg N ha −1 yr −1 ) and found that herbivore removal increased aboveground plant C stocks, particularly in moss, shrubs and litter. Soil C storage increased with atmospheric N deposition, and this was moderated by the presence or absence of herbivores. In exclosures receiving above 11 kg N ha −1 year −1 , herbivore removal resulted in increased soil C stocks. This effect was typically greater for exclosures dominated by dwarf shrubs ( Calluna vulgaris ) than by grasses ( Molinia caerulea ). The same pattern was observed for ecosystem C storage. We used our data to predict C storage for a scenario of removing all large herbivores from UK heathlands. Predictions were made considering herbivore removal only (ignoring N deposition) and the combined effects of herbivore removal and current N deposition rates. Predictions including N deposition resulted in a smaller increase in UK heathland C storage than predictions using herbivore removal only. This finding was driven by the fact that the majority of UK heathlands receive low N deposition rates at which herbivore removal has little effect on C storage. Our findings demonstrate the crucial link between herbivory by large mammals and atmospheric N deposition, and this interaction needs to be considered in models of biogeochemical cycling.

Drivers of carabid functional diversity: abiotic environment, plant functional traits, or plant functional diversity? - Robin J. Pakeman; Jenni A. Stockan (Ecology, 2014)
Understanding how community assembly is controlled by the balance of abiotic drivers (environment or management) and biotic drivers (community composition of other groups) is important in predicting the response of ecosystems to environmental change. If there are strong links between plant assemblage structure and carabid beetle functional traits and functional diversity, then it is possible to predict the impact of environmental change propagating through different functional and trophic groups. Vegetation and pitfall trap beetle surveys were carried out across twenty four sites contrasting in land use, and hence productivity and disturbance regime. Plant functional traits were very successful at explaining the distribution of carabid functional traits across the habitats studied. Key carabid response traits appeared to be body length and wing type. Carabid functional richness was significantly smaller than expected, indicating strong environmental filtering, modulated by management, soil characteristics, and by plant response traits. Carabid functional divergence was negatively related to plant functional evenness, while carabid functional evenness was positively correlated to plant functional evenness and richness. The study shows that there are clear trait linkages between the plant and the carabid assemblage that act not only through the mean traits displayed, but also via their distribution in trait space; powerful evidence that both the mean and variance of traits in one trophic group structure the assemblage of another.

Optimizing Carbon Storage Within a Spatially Heterogeneous Upland Grassland Through Sheep Grazing Management - Stuart W. Smith; Charlotte Vandenberghe; Astley Hastings; David Johnson; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Ecosystems, 2014)

Milling plant and soil material in plastic tubes over-estimates carbon and under-estimates nitrogen concentrations - Stuart W. Smith; A. H. Jean Robertson; Andrew A. Meharg; Robin J. Pakeman; David Johnson; Sarah J. Woodin; René van der Wal (Plant and Soil, 2013)

Edaphic factors influence the longevity of seeds in the soil - Robin J. Pakeman; James L. Small; Lynne Torvell (Plant Ecology, 2012)

Trait assembly in plant assemblages and its modulation by productivity and disturbance - Robin J. Pakeman; Jack J. Lennon; Rob W. Brooker (Oecologia, 2011)

Multivariate identification of plant functional response and effect traits in an agricultural landscape - Robin J. Pakeman (Ecology, 2011)
Plant functional traits have been proposed as a linkage between the environmental control of vegetation and ecosystem function. Identification of traits that mediate the response of plant species to the environment is well established, but the identification of effect traits and the linkage between the two sets is less developed. This was attempted for a study of eight contrasting land uses in a marginal agricultural landscape where data on vegetation, management controls of the disturbance regime, and soil characteristics, including nitrogen release, were measured simultaneously with measures of ecosystem function such as litter decomposition rates and primary productivity on 30 sites. Trait data were assembled from databases, and an iterative multivariate approach using the three table (species, trait, environment) method RLQ was employed to identify a parsimonious set of traits that predict plant species responses to the environment and a parsimonious set of traits that link vegetation to ecosystem function. The lists of response and effect traits were similar, and where differences were observed, traits were usually highly correlated with at least one trait in the other list. This approach identified a small number of traits (canopy height, leaf dry matter content, leaf size, and specific leaf area) that provide a means of linking vegetation responses to environmental change with changes in ecosystem function. Other response traits included vegetative spread strategy, start of flowering, and seed terminal velocity, but within the system studied these traits were all significantly correlated to the traits shared between the response and effect lists.

Leaf dry matter content as a predictor of grassland litter decomposition: a test of the ‘mass ratio hypothesis’ - Robin J. Pakeman; Antonia Eastwood; Andrew Scobie (Plant and Soil, 2011)

The impacts of pollination mode, plant characteristics and local density on the reproductive success of a scarce plant species, Salix arbuscula - Rosalind F. Shaw; David A. Elston; Robin J. Pakeman; Mark R. Young; Glenn R. Iason (Plant Ecology, 2010)

Nesting preferences of the threatened wood ant Formica exsecta (Hymenoptera: Formicidae); implications for conservation in Scotland - Jenni A. Stockan; Shaila Rao; Robin Pakeman (Journal of Insect Conservation, 2010)

Leaf traits capture the effects of land use changes and climate on litter decomposability of grasslands across Europe - Claire Fortunel; Eric Garnier; Richard Joffre; Elena Kazakou; Helen Quested; Karl Grigulis; Sandra Lavorel; Pauline Ansquer; Helena Castro; Pablo Cruz; JiŘí DoleŽal; Ove Eriksson; et al. (Ecology, 2009)
Land use and climate changes induce shifts in plant functional diversity and community structure, thereby modifying ecosystem processes. This is particularly true for litter decomposition, an essential process in the biogeochemical cycles of carbon and nutrients. In this study, we asked whether changes in functional traits of living leaves in response to changes in land use and climate were related to rates of litter potential decomposition, hereafter denoted litter decomposability, across a range of 10 contrasting sites. To disentangle the different control factors on litter decomposition, we conducted a microcosm experiment to determine the decomposability under standard conditions of litters collected in herbaceous communities from Europe and Israel. We tested how environmental factors (disturbance and climate) affected functional traits of living leaves and how these traits then modified litter quality and subsequent litter decomposability. Litter decomposability appeared proximately linked to initial litter quality, with particularly clear negative correlations with lignin‐dependent indices (litter lignin concentration, lignin : nitrogen ratio, and fiber component). Litter quality was directly related to community‐weighted mean traits. Lignin‐dependent indices of litter quality were positively correlated with community‐weighted mean leaf dry matter content (LDMC), and negatively correlated with community‐weighted mean leaf nitrogen concentration (LNC). Consequently, litter decomposability was correlated negatively with community‐weighted mean LDMC, and positively with community‐weighted mean LNC. Environmental factors (disturbance and climate) influenced community‐weighted mean traits. Plant communities experiencing less frequent or less intense disturbance exhibited higher community‐weighted mean LDMC, and therefore higher litter lignin content and slower litter decomposability. LDMC therefore appears as a powerful marker of both changes in land use and of the pace of nutrient cycling across 10 contrasting sites.

Isolation of habitat patches limits colonisation by moorland Hemiptera - Nick A. Littlewood; Robin J. Pakeman; Sarah J. Woodin (Journal of Insect Conservation, 2009)

Does chemical composition of individual Scots pine trees determine the biodiversity of their associated ground vegetation? - Glenn R. Iason; Jack J. Lennon; Robin J. Pakeman; Vera Thoss; Joan K. Beaton; David A. Sim; David A. Elston (Ecology Letters, 2005)
Despite plant secondary metabolites being major determinants of species interactions and ecosystem processes, their role in the maintenance of biodiversity has received little attention. In order to investigate the relationship between chemical and biological diversity in a natural ecosystem, we considered the impact of chemical diversity in individual Scots pine trees ( Pinus sylvestris ) on species richness of associated ground vegetation. Scots pine trees show substantial genetically determined constitutive variation between individuals in concentrations of a group of secondary metabolites, the monoterpenes. When the monoterpenes of particular trees were assessed individually, there was no relationship with species richness of associated ground flora. However, the chemical diversity of monoterpenes of individual trees was significantly positively associated with the species richness of the ground vegetation beneath each tree, mainly the result of an effect among the non‐woody vascular plants. This correlation suggests that the chemical diversity of the ecosystem dominant species has an important role in shaping the biodiversity of the associated plant community. The extent and significance of this effect, and its underlying processes require further investigation.

The influence of soil-type, drought and nitrogen addition on interactions between Calluna vulgaris and Deschampsia flexuosa: implications for heathland regeneration - Andrea Britton; Rob Marrs; Robin Pakeman; Pete Carey (Plant Ecology, 2003)